ENHANCE LEARNING WITH TECHNOLOGY: EXPLORING COMBINATIONS OF LEARNING STRATEGIES - Aris Susanto; Loso Judijanto; Hevi Susanti; Mukti Ali; Aferiaman Telaumbanua (International Journal of Teaching and Learning, 2024)
The presence of information technology has had an impact on changes in all aspects of Indonesian society's life, especially in the learning process. There are several learning strategies that teachers/lecturers can use in the technological era, including developing models, innovating and evaluating learning using digital media. With this technology era learning strategy, it is hoped that lecturers/teachers and students will find it easier to learn. This research aims to find out how to explore the combination of technology with learning strategies. This research method uses a systematic and iterative approach to gather a comprehensive understanding of topics related to technology, exploration of a combination of learning strategies. The conclusion of this research is that several effective learning strategies that involve technology are visualization, cooperative learning, and the use of technology in the classroom.